The Impact of Social Media Use on Adolescent Communication Patterns in Muara Binuangeun Village, Lebak Regency - Rince Karoline; Lala Febriyanti (MID Publisher International, 2024)
This study aims to analyze the impact of social media use on the communication patterns of adolescents in Muara Binuangeun Village, Wanasalam District, Lebak Regency. Social media has become an essential part of adolescents’ lives and plays a significant role in shaping the way they interact and communicate. This research employed a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews, observations, and documentation involving 15 adolescents who actively use social media. Informants were selected using purposive sampling based on the criteria of being 17–23 years old and actively using social media platforms such as WhatsApp, Instagram, Facebook, and TikTok. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, which includes data condensation, data display, and conclusion drawing. The findings indicate that social media has transformed adolescents’ communication patterns from face-to-face interaction to more flexible and rapid digital communication. WhatsApp emerged as the most frequently used platform for daily communication activities. Positive impacts include easier communication, broader social networks, increased access to information, and more frequent interactions. However, negative impacts were also identified, including reduced face-to-face communication, tendencies toward social media dependency, disruption of daily activities, and exposure to negative content and unverified information. The study concludes that social media significantly influences adolescents’ communication patterns, highlighting the importance of digital literacy and guidance from families and communities to ensure its optimal use.